DIAGNOSTIC AND THERAPEUTIC UTILITY OF GONADOTROPHIN-RELEASING HORMONE AGONIST IN POSTMENOPAUSAL HYPERANDROGENISM OF OVARIAN ORIGIN - Zainol, Muhammad Qyairil Anwar Che; Shafie, Rosliza; Abdull, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Postmenopausal hyperandrogenism can be due to excessive androgen secretion from adrenal or ovarian virilizing tumours or nonneoplastic conditions, manifesting as increased terminal hair growth or virilization. Ovarian androgen secretion is usually nonautonomous and stimulated by gonadotrophins. The administration of a gonadotrophin-releasing Hormone (GnRH) agonist would suppress the production of androgen. GnRH agonist has been advocated as a diagnostic tool to distinguish between adrenal and ovarian hyperandrogenism. We described a patient with postmenopausal hyperandrogenism who was commenced on GnRH agonist with significant androgen suppression pointing towards ovarian in origin. CASE A 71-year-old female presented with hirsutism and acne for 2 years. Her Ferriman Gallwey score was 11 with the absence of hoarseness of voice, androgenic alopecia or clitoromegaly. Investigations revealed FSH 23.6 IU/L (26-133), LH 7.54 IU/L (5.16-61.99), oestradiol 40 pmol/L (0-28), testosterone 37.17 nmol/L (0.46-1.18), DHEAS 2 µmol/L (0.26-6.68), 17OHP 4.17 nmol/L (1-8.2), overnight dexamethasone suppression test (ODST) 27.6 nmol/L, fT4 10.78 pmol/L (9-19), TSH 0.69 mIU/L (0.35-4.94), sex hormone binding globulin (SHBG) 39 nmol/L (30 90), free androgen index (FAI) 47.26 (7-10). CT scan of the thorax, abdomen and pelvis revealed normal adrenal glands and bilateral ovaries. Transvaginal ultrasound demonstrated normal ovaries. She was initiated on leuprorelin injection 11.25 mg every 3 months and then switched to triptorelin 3.75 mg every month due to stock shortage. Following the first dose of GnRH agonist, testosterone dramatically reduced to 0.53 nmol/L (98.6% reduction), FSH reduced to 12.4 IU/L (47.5%), and LH reduced to 0.27 IU/L (96.4%) with clinical improvement. The possibility of adrenal hyperandrogenism was ruled out with normal ODST, 17OHP, DHEAS and CT findings. An ovarian source of androgen excess was further confirmed by the marked suppression of testosterone by the GnRH agonist. The histopathological diagnosis of ovarian hyperandrogenism could not be determined as she was not keen for bilateral oophorectomy. CONCLUSION Postmenopausal hyperandrogenism requires comprehensive assessment. GnRH agonist can be used in the evaluation and it can be adopted as a potential conservative treatment for patients who refuse or are not fit for surgery.